ANALISIS BIAYA PENYUSUTAN PADA PROSES PENGERINGAN PASCAPANEN PADI DI KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Selvy Friana Sary; Zainal Abidin; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to analyses the cost of influencing factors and effort to reduce the loss in paddy drying.  The study is conducted by survey method in which 40 respondents are selected by simple random sampling.  Descriptive quantitative analysis is used to determine the cost of loss in paddy drying process.  KHP method is used to determine the loss.  Linear Regression is used to estimate affecting factors on the loss paddy drying process.  Descriptive qualitative analysis was used to understand efforts conducted by farmers to reduce loss. The study showed that cost got by farmers of the average 0.50 hectare area was Rp435,070/farmer in a planting season.  The loss influencing factors in paddy post-harvest drying process were total production, thickness of drying layer, the use of drying media and weather.  Farmers effort to reduce the loss in paddy drying process consists of arranging thickness of paddy drying, the wide of media drying, the length of drying process, reversing paddy, monitoring, maintaining of drying floor, and directing paddy expose to the sun.Key words: economic loss, loss in paddy, paddy drying process, paddy post-harvest